Высокочастотный источник накачки активных сред на парах металлов; Приборы и техника эксперимента; № 1 - Торгаев С. Н. Станислав Николаевич; Огородников Д. Н. Дмитрий Николаевич; Мусоров И. С. Илья Сергеевич; Кулагин А. Е. Антон Евгеньевич; Евтушенко Г. С. Геннадий Сергеевич (2020, 2020)
Заглавие с экрана